Intestinal microbiota modulation at the strain level by the olive oil polyphenols in the diet - Andújar-Tenorio, Natalia; Cobo, Antonio; Martínez-Rodríguez, Ana Mª; Hidalgo, Marina; Prieto, Isabel; Gálvez, Antonio; Martínez-Cañamero, Magdalena (Frontiers in Nutrition, 2023)
Introduction: Previously we have reported a r16S gene next generation sequencing study on the effect of high fat diets in the intestinal microbiota using a murine model. However, many important microbial traits occur at strain level and, in order to detect these population changes, culture-dependent approaches need to be applied. With this goal, we decided to study a very well-known commensal genus, Enterococcus, and therefore, intestinal enterococci methodically isolated during the abovementioned experiment were analyzed. Materials and Methods: A collection of 75 distinct enterococcal strains isolated from faeces of mice fed a standard diet or high-fat diets enriched with butter, refined olive oil, or extra virgin olive oil and after 0, 6 or 12 weeks of diet, were genetically and phenotypically characterized in search of virulence factors, biogenic amine production and antibiotic resistance. All strains were tested for the susceptibility in vitro to two virgin olive oil polyphenols, oleuropein (the bitter principle of olives) and hydroxytyrosol (derived from oleuropein by enzymatic hydrolysis and responsible for the high stability of olive oil). Results: No drastic polyphenol effect was found except at high concentrations. However, when carrying out a comparative statistical study in the 75 strains of the collection according to the different diets, we have detected significant differences between the strains isolated from mice fed with a diet enriched with virgin olive oil and the rest of the diets. EVOO strains also presented less resistance to antibiotics and a more beneficial profile overall. Discussion: These results support the prebiotic role of polyphenols, showing how they are able to modulate the set of strains that comprises a genus in the gut, allowing them to adapt to a changing environment in the host's intestine and possibly exerting effects on its physiology Con formato: Fuente: Cursiva